PENGEMBANGAN TEKNOLOGI DALAM DESAIN PEMBELAJARAN PAI - Rayhani, A.; Hanapi, Wahyu; Cahyadi, Ani (Berajah Journal, 2024)
The use of technology in Islamic religious education (PAI) has become a primary focus in developing effective and relevant teaching methods. This article explores the integration of technology in the design of PAI learning to enhance student engagement and teaching efficiency. A literature review identifies that traditional approaches in PAI education can be enhanced through digital technology, such as interactive applications, e-learning platforms, and social media, which support interaction and deeper understanding of religious teachings. Qualitative research methods were employed to evaluate the implementation of technology in PAI learning at secondary schools. The findings indicate that integrating technology not only increases students' interest in PAI subjects but also expands their access to a wider range of educational resources. The practical implications of this research emphasize the importance of training educators to adopt technology as a tool to enhance the PAI learning experience. This study provides guidance for curriculum developers and educational policymakers to harness the potential of technology in supporting holistic and effective Islamic religious education.